Pengaruh Pemberdayaan Karyawan dan Kepuasan Kerja Terhadap Produktivitas Perusahaan di Toyota Auto2000 Tanjung Api-Api Palembang - Muhammad Tio Septa Syafril (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2022)
This study aims to analyze the effect of employee empowerment and job satisfaction on company productivity at Toyota Auto 2000 Tanjung Api-Api Palembang. Primary data used in this study were obtained from a questionnaire filled out by 178 respondents. Then the data is processed using multiple linear regression analysis method. The results indicates that employee empowerment (X1) and job satisfaction (X2) had a significant positive effect on company productivity (Y). This research is expected to become literature on the topic of employee empowerment, job satisfaction and company productivity.